Are you threatening me? Development and validation of the Conflict Escalation Questionnaire - Scheppa-Lahyani, Miriam Nicole; Zapf, Dieter (Frontiers in Psychology, 2023)
This study aimed to develop and validate an instrument for measuring conflict escalation based on Glasl’s conflict escalation model, which can also be used for measuring bullying conflicts. The instrument should be applicable both as self-assessment and as interviewer-assessment. In a first study, a first set of items measuring the stages of Glasl’s model was developed and validated in an independent cross-sectional sample of 154 participants who completed the self-assessment. In 142 cases, interviews were conducted, and thus self and interviewer-assessments could be compared. In a second study, the final set of items was cross-validated on a second independent cross-sectional sample. 105 participants completed the self-assessment only and 114 were part of the interview study. Because Glasl’s model is complex, scale validation was based on a combination of classical statistical validation procedures. Both studies indicate good validity of the new instrument and provide evidence for Glasl’s conflict escalation model. As expected, conflict escalation was positively related to negative affect, irritation, and depression. Relationship conflict was more prevalent in more highly escalated conflicts as compared to lower escalated conflicts. Victims of workplace bullying were classified in high escalation levels and showed higher inferiority in conflict situations compared to non-victims with highly escalated conflicts. The present instrument can be used to assess qualitative differences in conflict escalation, and thus complements existing instruments to measure conflicts. It is especially useful for practitioners, as they can assess conflict escalation more accurately and thus better choose the appropriate form of intervention.